1989
DOI: 10.1111/j.1460-2695.1989.tb00530.x
|View full text |Cite
|
Sign up to set email alerts
|

A Crack Closure Study to Predict the Threshold Behaviour of Small Cracks

Abstract: The small crack problem is addressed within the applicability of Linear Elastic Fracture Mechanics as the result of crack closure phenomenon. The variation of crack closure stress intensity factory Kop as a function of crack length, a, was determined in two materials, namely a A508 steel and a 2024A1 alloy. These results were obtained on two-dimensional small cracks (a 3 0.1 mm) which were machined from long fatigue cracks. These measurements of Kop in addition to data published in the literature on a nodular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…have to be fitted by a proper law. It has been found that the commonly used exponential law (see Journet et al and McEvily et al) normalΔKth=normalΔKth,italicop+normalΔKth,italiceff=()1eprefix−knormalΔa()normalΔKth,LCnormalΔKth,italiceff+normalΔKth,italiceff did not yield a satisfactory approximation of the data in the initial part of the R ‐curve. A better fitting has been obtained employing a power law, which then resulted in the following expression: normalΔKthnormalΔKth,LC={center0.856normalΔa0.198normalfnormalonormalr0.25emnormalΔa<2.20.25emnormalmmcenter14.75emnormalfnormalonormalr0.25emnormalΔa2.20.25emnormalmm for the present material.…”
Section: Proposal For the Determination Of The Initial Crack Sizementioning
confidence: 96%
See 1 more Smart Citation
“…have to be fitted by a proper law. It has been found that the commonly used exponential law (see Journet et al and McEvily et al) normalΔKth=normalΔKth,italicop+normalΔKth,italiceff=()1eprefix−knormalΔa()normalΔKth,LCnormalΔKth,italiceff+normalΔKth,italiceff did not yield a satisfactory approximation of the data in the initial part of the R ‐curve. A better fitting has been obtained employing a power law, which then resulted in the following expression: normalΔKthnormalΔKth,LC={center0.856normalΔa0.198normalfnormalonormalr0.25emnormalΔa<2.20.25emnormalmmcenter14.75emnormalfnormalonormalr0.25emnormalΔa2.20.25emnormalmm for the present material.…”
Section: Proposal For the Determination Of The Initial Crack Sizementioning
confidence: 96%
“…by a proper law. It has been found that the commonly used exponential law (see Journet et al 16 and McEvily et al 17 )…”
Section: The Cyclic R-curvementioning
confidence: 99%
“…The data points had to be fitted by a proper law to be used in a resistance curve analysis. The existing works in the literature dealing with this issue, propose a fitting with an exponential law [21,22]. The use of these laws in case of our data points did not provide a satisfactory approximation in the mechanically short crack regime, which is the most important to the goal of the present work, as it is the region in which non-propagating cracks occur.…”
Section: Experimental Derivation Of the Cyclic R-curvementioning
confidence: 83%
“…The exact transition point, when crack closure becomes stationary, depends on the material and can vary between some hundred micrometres to millimetres (see [57]). A very rough guide value is a depth of 0.5 mm and a length at surface of 1 mm in the case of semi-elliptical surface cracks in medium strength steel [58].…”
Section: Small Cracksmentioning
confidence: 99%